Concerns, perceived impact, and preparedness of oral healthcare workers in their working environment during COVID‐19 pandemic. Issue 1 (20th September 2020) - Chaudhary, Farooq Ahmad; Ahmad, Basaruddin; Ahmad, Paras; Khalid, Muhammad Danial; Butt, Danial Qasim; Khan, Soban Qadir
Abstract: Objective: The aim of the study was to evaluate the oral healthcare workers' concerns, perceived impact, and preparedness in COVID‐19 pandemic. Methods: This cross‐sectional study was carried out at 10 different dental hospitals in Pakistan from March to June 2020. A 35 items valid and reliable questionnaire was used to assess the concerns, perceived impact, and preparedness of oral healthcare workers (OHCW) in COVID‐19 pandemic. Chi‐squared test and logistic regression were used for analysis. Results: A total of 583 OHCW participated in this study. The odds of having the awareness about the risk of exposure and fear of getting infected, were greater in the clinical than non‐clinical OHCW (OR: 52.6; OR: 15.9). For social network concerns, the clinical OHCW were more likely to be concerned about their colleagues (OR: 6.0). The clinical OHCW have greater odds of worrying about telling the family/friends about the risk exposed to (OR: 2.55), being avoided because of the job (OR: 3.20) and more likely to be feeling stressed (OR: 4.31). Less than 50% of the participants felt that their institutions are well prepared and only 12.6% had attended an infection control training session. Most participants practiced self‐preparation such as buying masks and disinfection (94.3%, 98.3%). Conclusion: The majority of OHCW felt concerned about their risk of exposure to infection and falling ill from exposure and infecting friends/family. There is a need for training of infection control and PPE and minimizing fear and psychological impact on OHCW should be the priority in any preparedness and planning for combating COVID‐19.